Using Technology in Teaching English Language: Perceptions of Teachers and Students - Nasution, Faisal; Efrina Nasution, Linda; Rifai Rangkuti, Ahmad (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
The integration of technology in English language teaching has brought about a paradigm shift in educational methodologies. It offers a diverse range of tools and resources that facilitate interactive, flexible, and student-centered learning environments. This study explores the perceptions of teachers and students on the use of technology in English language education, focusing on its benefits, challenges, and overall impact. Teachers perceive technology as a valuable aid in enhancing student engagement and providing access to authentic language materials, while also expressing concerns about dependency, technical issues, and unequal access. Students, on the other hand, appreciate the interactivity and flexibility provided by technological tools but acknowledge distractions and over-reliance as potential drawbacks. The research employs qualitative methods, including semi-structured interviews with teachers and focus group discussions with students, to uncover nuanced perspectives. Findings indicate that while technology enhances accessibility and personalized learning, its effectiveness depends on factors such as teacher preparedness, balanced usage, and equitable access. This study underscores the need for professional development for educators and strategic policies to address disparities in access. A balanced approach combining traditional and technological methods is recommended to optimize the potential of digital tools in English language teaching